The impact of the prolonged COVID-19 pandemic on adolescents with eating disorders: a follow-up study from Türkiye - Erdem Torun, Şeyma; Akgül, Sinem; Pehlivantürk Kızılkan, Melis; Nalbant, Kevser; Kanbur, Nuray; Akdemir, Devrim; Ersöz Alan, Burcu; Tüzün, Zeynep; Derman, Orhan (The Turkish Journal of Pediatrics, 2024)
Background. At the onset of the pandemic, we conducted a study on adolescents with eating disorders (EDs) and found no deterioration in ED symptoms. The objective of this subsequent study was to conduct a follow-up evaluation of the same cohort and investigate the consequences of the prolonged pandemic. Methods. This longitudinal study was conducted one year after the first study between May 2021 and June 2021 with 37 adolescents aged 12-18 years (pre-existing EDs). The reassessment included an evaluation of sociodemographic and clinical characteristics, the impact of pandemic-related restrictions on ED behaviors, well-being, and quality of life. All the participants underwent a re-administration of the ED examination questionnaire (EDE-Q), Beck Depression Inventory, the State Anxiety Inventory for Children, and the Maudsley Obsessive Compulsive Inventory. Results. No significant difference was observed in the EDE-Q scores or the ED examination questionnaire scores between the initial (T1) and subsequent (T2) study. The ED-related quality of life was seen to have slightly improved in the later stage. While depression (T1: 18, T2: 15, p=0.883) and obsession scores (T1: 11, T2: 14, p: 0.536) showed no disparity between the studies, anxiety scores (T1: 38, T2: 43, p:0.011) exhibited a significant increase. Conclusions. Consistent with the early phase, no exacerbation of ED symptoms in adolescents was observed during the later stages of the pandemic. Close clinical monitoring during the pandemic might have been protective against the deteriorating effects of the pandemic. During social isolation, it is important to monitor adolescents with EDs continously for depression and anxiety.